2012
DOI: 10.1590/s1517-83822012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of tyrosinase activity in Pycnoporus sanguineus CCT-4518 crude extract

Abstract: Tyrosinase is an enzyme of industrial interest. The production and characterization of tyrosinase from P. sanguineus CCT-4518 were investigated. The selection of inductors, luminosity influence, inoculum size and type of culture medium on the production of tyrosinase and the effect of inhibitors on enzyme activity were performed. Optimum conditions for intracellular tyrosinase production was observed after 2 days using 0.15% L-tyrosine as inducer, in the presence of light, with inoculum size of 10 mycelium dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…B13, respectively. The factors affecting our findings may not be precisely identifiable at the moment, however, our deduction disagrees with the observations of Duarte et al [29] and Valipour and Arikan [23], who reported 48 h and 16 h optima for Pycnoporus sanguineus and Bacillus megaterium, respectively.…”
Section: Optimization Studies On Tyrosinase Productioncontrasting
confidence: 99%
“…B13, respectively. The factors affecting our findings may not be precisely identifiable at the moment, however, our deduction disagrees with the observations of Duarte et al [29] and Valipour and Arikan [23], who reported 48 h and 16 h optima for Pycnoporus sanguineus and Bacillus megaterium, respectively.…”
Section: Optimization Studies On Tyrosinase Productioncontrasting
confidence: 99%
“…The thermostability of the tyrosinase from L. pulmonaria resembles that of the enzyme from free-living fungi (e.g. Duarte et al 2012) (Fig. 4).…”
Section: Kinetics Of Tyrosinase and Other Redox Enzymesmentioning
confidence: 84%
“…The latter finding is somewhat unexpected since enzyme activity, e.g. the activity of tyrosinase, is related to temperature and becomes reduced below 37°C (Boron & Boulpaep, 2012; Duarte et al, 2012). However, a possible cause of the lower percentage of pigment-containing cells found at higher storage temperatures could be poorer cell integrity at these temperatures, with subsequent loss of pigment granules to the extracellular space.…”
Section: Discussionmentioning
confidence: 99%